International Pediatric Otolaryngology Group (IPOG) consensus recommendations: Hearing loss in the pediatric patient. (November 2016) - Liming, Bryan J.; Carter, John; Cheng, Alan; Choo, Daniel; Curotta, John; Carvalho, Daniela; Germiller, John A.; Hone, Stephen; Kenna, Margaret A.; Loundon, Natalie; Preciado, Diego; Schilder, Anne; et al.
Abstract: Objective: To provide recommendations for the workup of hearing loss in the pediatric patient. Methods: Expert opinion by the members of the International Pediatric Otolaryngology Group. Results: Consensus recommendations include initial screening and diagnosis as well as the workup of sensorineural, conductive and mixed hearing loss in children. The consensus statement discusses the role of genetic testing and imaging and provides algorithms to guide the workup of children with hearing loss. Conclusion: The workup of children with hearing loss can be guided by the recommendations provided herein.